State-level Citizen Response to COVID-19 Containment Measures in Brazil and Mexico - Claire Dunn; Isabel Laterzo (Journal of Politics in Latin America)
In Brazil and Mexico, presidents failed to take swift, national action to stop the spread of COVID-19. Instead, the burden of imposing and enforcing public health measures has largely fallen to subnational leaders, resulting in varied approaches within each country and conflicting messaging from elites. We likewise see variation in compliance with social distancing across subnational units. To explain this variation, we contend that citizen responses are driven both by the comprehensiveness of state policies and whether they take cues from national or subnational elites. We hypothesize that support for national and subnational elites, and the nature of the state-level policy response, affect citizen compliance with public health guidelines. In both countries, we find that support for the governor has an interactive relationship with policy response. In Brazil, support for the president is associated with lower compliance. In Mexico, this effect is not present. We argue that these distinct relationships are due to the different cues emerging from each leader.